Examination of Algebraic Thinking Levels of Middle School Students - Neslihan Usta; Burçin Gökkurt Özdemir (Anı Publishing, 2018)
The aim of this study is to examine the algebraic thinking levels of middle school students. In this research based on the qualitative approach, the case study method among qualitative research approaches was made. Clinic interviews were made as a qualitative data collection technique, and the interviews held were voice recorded. This study was carried out with middle school students (6th, 7th and 8th-grade) studying at a state school in a province of Western Black Sea Region. The study group consists of 12 students chosen with purposive sampling method. In this context, An Algebraic Thinking Level Determination Form (ATLDF) consisting of eighth questions in total were prepared by choosing two questions for each of the four levels as data collection tool. In the analysis of the data, qualitative analysis techniques were used. At the end of the study, it was seen that students generally give correct answers on the questions regarding the 1st and 2nd levels, but they have more difficulty in answering the questions on the 3rd and 4th levels. Results of the study indicate that all 12 students were able to answer correctly first and second questions in Level-1. Students thought the letters as objects in their Level-1 answers and were able to finalize the operation without giving any numerical value to the letters in the questions. Some students tried to find a result by giving numerical values to given figure's circumference length whose circumference length is unknown for the fourth question in Level-2. The situation has been seen that the fifth and sixth questions, related to algebraic thought's Level-3, were challenged by 7th grade students. At this level the letters must be perceived as unknown. However students gave numerical values to letters and tried to solve the questions. It was seen that some students who are unable to give the correct answers to the questions in Level-4 have misconception that the multiplication process will increase the value of the algebraic expression when their explanations for sixth question's answers were examined.